Evaluasi Media Panduan Pembelajaran Jarak Jauh Bagi Anak Penyandang Disabilitas - Amin, Abdul; Rosta Rosalina (HERITAGE, 2022)
The pandemic COVID-19 has encouraged the implementation of distance learning (DL) which is applied to all, including children with disabilities. The DL guidelines were launched by the Ministry of Education and Culture in order to continue to fulfill the disability right to education. This literature study research analyzes the evaluation of media using the QUOTA (Qualified, Up to date, Objectivity, True, Accurate) approach. The results show that guidance is good enough as a first step in providing information for parents, educators, and children. Along with the challenges and obstacles of DL felt by all parties, the DL guidelines for children with disabilities need to be updated regularly and adjusted to the situations and obstacles that arise in the implementation of DL Keywords: children, COVID-19, disability, distance learning, guidelines